A comparative study of the infallibility of the Messenger of God  from the perspective of Tabarsi and Fakhr al-Razi (relying on the interpretation of the collection of statements and the keys of the unseen) - sayyedsajjad jafari (پژوهش‌نامه کلام تطبیقی شیعه, 2022)
The issue of the infallibility of the prophets is one of the topics that has always been disputed between the Imams and the Sunnis in its scope and scope. , Often due to the appearance of some verses do not believe in the infallibility of the Prophet. In all respects. The present article is descriptive-analytical, and using library sources to compare the views of Fakhr Razi, one of the Sunni commentators on theological issues, and Tabarsi, one of the great Imami commentators on the following verses; 105 and 106 of Surah An-Nisa '; 49 سوره مائده 43 سوره توبه; 52 سوره حج; 37 سوره احزاب; 2 سوره فتح می‌پردازد. Tabarsi, like most Imams, believes that the Prophet  is infallible and that this infallibility existed before and after the prophecy, while Fakhr al-Razi, according to the appearance of the verses, believes that infallibility is not necessary for the Prophet قبل before the resurrection, but it is necessary. It is from the time of revelation.